The history and the development of the chair of infectious diseases in children (By 20th Anniversary of the chair of infectious diseases in children PSI and PR of the SEI HPE SSPMA Roszdrav) - N. V. Skripchenko; V. V. Ivanova (Журнал инфектологии, 2014)
In the article described stages of formation and different lines of activity of the chair of infectious diseases in children of faculty of professional skill improvement and professional retraining of the St-Petersburg State Pediatric Medical Academy during 20 years. Personal data of employees of the chair and their scientific interests are presented.